2015
DOI: 10.1021/jacs.5b06658
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Mediated Crystallization of CH3NH3SnI3Films for Heterojunction Depleted Perovskite Solar Cells

Abstract: Organo-lead halide perovskite solar cells have gained enormous significance and have now achieved power conversion efficiencies of ∼20%. However, the potential toxicity of lead in these systems raises environmental concerns for widespread deployment. Here we investigate solvent effects on the crystallization of the lead-free methylammonium tin triiodide (CH3NH3SnI3) perovskite films in a solution growth process. Highly uniform, pinhole-free perovskite films are obtained from a dimethyl sulfoxide (DMSO) solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
601
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 666 publications
(615 citation statements)
references
References 61 publications
6
601
1
7
Order By: Relevance
“…PCEs of 6.4% and 5.73% were reported, respectively, and after three years they are still the record efficiencies among MASnX 3 ‐based PSCs (Figure 3c). This dramatic different situation from the lead‐based perovskite can be understood by the fact that Sn‐based perovskites are prone to self‐doping in ambient air resulting in instability and poor reproducibility 46, 47, 48, 51, 52, 53, 135…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
See 2 more Smart Citations
“…PCEs of 6.4% and 5.73% were reported, respectively, and after three years they are still the record efficiencies among MASnX 3 ‐based PSCs (Figure 3c). This dramatic different situation from the lead‐based perovskite can be understood by the fact that Sn‐based perovskites are prone to self‐doping in ambient air resulting in instability and poor reproducibility 46, 47, 48, 51, 52, 53, 135…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
“…The author has concluded that the SnF 2 cannot only improve interfacial energy alignment but also increase stability to electron beam damage. Nowadays, most Sn‐based perovskites films prepared by solution deposition need additional SnF 2 to get good performance,47, 48, 57, 58, 73 including the recent (FA) 0.75 (MA) 0.25 SnI 3 based PSCs with the highest PCE of 8.12% 56. Additionally, Ma et al134 claimed that SnF 2 as the inhibitor of Sn 2+ oxidation in the MASnI 3 film could increase the fluorescence lifetime up to 10 times and give longer carrier diffusion lengths >500 nm, compared with pristine MASnI 3 films.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, SnF 2 , as an additive, has been found to effectively suppress the doped hole density in Sn‐based perovskites and improve device stability and reproducibility 16, 17. The use of dimethyl sulfoxide (DMSO) as the precursor solvent has proven to be crucial in acquiring homogeneous films, as it forms a SnI 2 ·3DMSO intermediate phase that retards the rapid crystallization of Sn‐based perovskites 18. Seo and co‐workers employed a SnF 2 ‐pyrazine complex to improve the morphology of FASnI 3 films and obtained a PCE of 4.8% 19.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, researchers have begun to explore related materials with a lower toxicity and/or better stability. [6][7][8] Meanwhile, the past few years have seen the renaissance of photoferroelectric materials for PV applications. [9][10][11][12] Photoferroelectric materials, such as BiFeO 3 and SbSI, are semiconducting ferroelectrics that show both photosensitive and ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%